Inferior gastroschisis - Patel, Ramnik V (BMJ Publishing Group, 2013)
Gastroschisis is a common defect of the central abdominal wall, nearly always located to the right of the umbilicus. We report a baby boy with gastroschisis who had a defect on the inferior side of an intact and normal umbilical cord which was managed by primary repair and an uneventful recovery. Such a case has never been reported in the literature. This case contributes towards enlarging the spectrum of gastroschisis.